Karl Heim se verstaan van ruimte in die debat tussen die teologie en natuurwetenskap - Buitendag, Johan (Verbum et ecclesia, 2002)
Karl Heim’s understanding of ‘space’ in the debate between theology and natural sciences This article gives a brief synopsis of Karl Heim’s understanding of space in terms of its present and past spheres and the overarching metapolar sphere of God where all dichotomies are being resolved. The rather clas-sical booklet of Edwin Abbott, ‘Flatland’, is used as an introduction to indicate the importance of understanding reality in terms of dimensions and the expanding thereof. It makes sense to consider this as a point on the agenda in the dialogue between theology and natural sciences. The author points out thatHeim’s concept of space finds its way both in phi-losophy and theology inter alia in the works of Deleuze and Kasper re-spectively.